The extent to which Saudi E-newspapers adhere to professional media standards - Meliani, Kholoud Abdullah Mohammed (Journal of Economic, Administrative and Legal Sciences, 2017)
The emergence of the press on the Internet is a new media phenomenon linked to the revolution of information and communication technology. The media landscape has become closer to everyone. The role of the individual is free from the production controls and the policies of the media establishment. Which created a great problem related to the profession and its conditions so that it became easy for the citizen to be a journalist without professional qualification and practical experience in the basic rules of work. The increasing number of electronic media and the impact on Saudi Arabia are an important stage in its media activity. It has been able to reflect a significant role in the world of journalism, to accelerate the use of these new technologies, and to impose itself on the media arena as a strong competitor for paper journalism. However, the multiplicity of electronic platforms, accompanied by many negative repercussions in this aspect, including the absence of professionalism and professionalism and the decline in journalism standards, especially in the climate of freedom enjoyed by the new media and the absence of scissors censor. The aim of this study was to identify the methods and means of communicators in the electronic press to achieve professional standards such as accuracy, credibility, objectivity and neutrality in the dissemination of news and reports through the use of descriptive and analytical approach through the field survey on a sample of the study community. The study relied on the questionnaire as a tool for collecting data from a sample of 120 Saudi journalists in electronic newspapers and then analyzing and interpreting them. The study reached several results, the most important of which is that there is weakness in the adoption of the Saudi electronic press to the professional standards of objectivity, accuracy, credibility, and impartiality in the dissemination of news and reports. The study also concluded that e-newspapers do not always adhere to the rules of journalistic editing, and sometimes publish what is considered a violation of personal freedom.